2023
DOI: 10.1037/aca0000465
|View full text |Cite
|
Sign up to set email alerts
|

Melody in poems and songs: Fundamental statistical properties predict aesthetic evaluation.

Abstract: Since antiquity, the concept of melody has been related not only to music, but also to language, specifically poetic language. However, while melodic properties of music were already mathematically defined more than 2,000 years ago, melodic properties of poems have remained fairly elusive to date. Proceeding from the assumption that fundamental melodic properties should in both domains be measurable in terms of recurrent time series of pitch and duration values, we administered two statistical measures-(a) aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 83 publications
1
17
0
Order By: Relevance
“…The program of computational textual aesthetics has been heavily influenced by relevant studies from other domains. For example, statistical properties of (time) series have been analysed for music [ 31 ], poetry [ 49 ], and even bird song [ 50 ]. Measures such as autocorrelation, variability, surprise and predictability have also been used to predict musical preferences in humans [ 30 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The program of computational textual aesthetics has been heavily influenced by relevant studies from other domains. For example, statistical properties of (time) series have been analysed for music [ 31 ], poetry [ 49 ], and even bird song [ 50 ]. Measures such as autocorrelation, variability, surprise and predictability have also been used to predict musical preferences in humans [ 30 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…When considering the role that stimulus features play in aesthetic judgments, it is first important to touch on the different levels that the word “feature” can denote. As shown in Scharinger et al, 2023, features can mean low-level acoustic features. Alternatively, the term “feature” has also been used to refer to subjective ratings of perceptual features (i.e., loudness, roughness), or even ratings of higher-level features such as the emotional qualities of a piece of music.…”
Section: The Context—live Concertsmentioning
confidence: 99%
“…The third and final live concert study focuses on similarities (and differences) between songs and poems experienced during a live concert (Scharinger et al, 2023). In this study, audience members attended a concert in which a series of poems were both recited orally and sung with a piano accompaniment.…”
Section: The Context-live Concertsmentioning
confidence: 99%
“…While empirical aesthetics has traditionally focused on visual stimuli, the field has progressed in recent years as researchers have begun investigating the subjective experience of artistic products in many different sensory and creative domains. For example, recent work has explored the aesthetic experience of artistic products such as architecture (Dai et al, 2022; Skov et al, 2022), dance (Calvo-Merino, 2021; Monroy et al, 2022), films (Muth et al, 2015), music (Brattico & Pearce, 2013; Omigie et al, 2021), and poetry (Kraxenberger & Menninghaus, 2017; Scharinger et al, 2023). Much of this work has focused on the features driving aesthetic judgments of these various types of art.…”
mentioning
confidence: 99%
“…Perhaps due to their similarities in terms of temporal evolution and rhythmic properties, poetry and music are two domains that have previously been compared. For example, Scharinger et al (2023) had audience members rate their experience of songs and poems heard at a performance. Their results indicated that perceived (i.e., subjective) melodiousness predicted aesthetic appeal of both poems and songs (Scharinger et al, 2023).…”
mentioning
confidence: 99%